Removal of Heavy Metal Ions from Industrial Wastewater Using Activated Carbon Derived from Rubber Seed Shell - Abdullah, Nur Atikah (IRC, 2015)
Rubber plantation is the second largest plantation in Malaysia where produced a large amount of rubber seed shell as a waste. To prevent odour pollution caused by the waste, a research was conducted to produce an activated carbon. The raw rubber seed shell has high carbon content about 52.5% which fall between ranges to be a prospective activated carbon. Heavy metal ions exist in almost industries nowadays and using adsorption method, activated carbon derived from rubber seed shell is used to remove the heavy metals especially in electroplating industry. Electroplating industry is one of major contributing industry producing higher amount of heavy metal even though undergo wastewater treatment process. Electroplating industry produces a high percentage of effluent zinc and copper. The rubber seed shell was grinded and sieved into two different size which are 1mm and 500μm. The rubber seed shell then further heated using oven, furnace and other equipment using activation temperature of 500˚C and 600˚C and activation time of 90, 120, 150, 180 and 210 minutes. Sample B1 is the best activated carbon produced using activation temperature of 600˚C, activation time of 180 minutes using impregnation ratio 1:2 with activating agent sodium hydroxide, NaOH solution. The removal of heavy metals of zinc and copper from electroplating industry was investigated based on three (3) effects of initial concentration, effect of stirring rate and effect of contact time. With specific surface area of 28.17m2g−1 and pore diameter of 17.3nm, sample B1 removed zinc better than copper up to 99% of removal. From effect of initial concentration, sample B1 removed zinc up to 98.8% and copper up to 85%. For effect of stirring rate, percentage of zinc removal is 99.7% and copper is 99.6%. for effect of contact time, percentage of zinc removal is 99.6% and copper is 88%.